(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
The article examines the theoretical aspects of studying information and communication terminology in the context of the digitalization of modern society. The influence of information and communication technologies on the development of the lexical system of language and the formation of specialized ICT terminology is analyzed. Particular attention is paid to the problems of defining the term, its grammatical nature, and the main approaches to the study of terminological units in modern linguistics. The study investigates the most productive word-formation methods of information and communication vocabulary, including borrowing, abbreviation, clipping, and univerbation. The paper also discusses the peculiarities of the functioning of professionalisms and colloquial elements in digital communication.